2013
DOI: 10.1371/journal.pone.0059569
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a New Growth References for China Based on Urban Chinese Children: Comparison with the WHO Growth Standards

Abstract: IntroductionGrowth references for Chinese children should be updated due to the positive secular growth trends and the progress of the smoothing techniques. Human growth differs among the various ethnic groups, so comparison of the China references with the WHO standards helps to understand such differences.MethodsThe China references, including weight, length/height, head circumference, weight-for-length/height and body mass index (BMI) aged 0–18 years, were constructed based on 69,760 urban infants and presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 16 publications
6
123
0
Order By: Relevance
“…Comparing the final height and weight data with recent international studies from China, Saudi Arabia, WHO and CDC, it is clear that Indian children are growing almost at par with Chinese and Saudi Arabian children but are still shorter and lighter than their Caucasian counterparts [7,27,28,29] (Table VII and Web Table I). Further, Indian children's stature seems to be comparable to Caucasian children until the onset of pubertal years, however, the growth spurt after puberty is attenuated in Indian children in both sexes, the effect being more pronounced in girls.…”
Section: Discussionmentioning
confidence: 90%
“…Comparing the final height and weight data with recent international studies from China, Saudi Arabia, WHO and CDC, it is clear that Indian children are growing almost at par with Chinese and Saudi Arabian children but are still shorter and lighter than their Caucasian counterparts [7,27,28,29] (Table VII and Web Table I). Further, Indian children's stature seems to be comparable to Caucasian children until the onset of pubertal years, however, the growth spurt after puberty is attenuated in Indian children in both sexes, the effect being more pronounced in girls.…”
Section: Discussionmentioning
confidence: 90%
“…These results were consistent with other papers: Fredriks et al (2005) reported the correlation coefficients were À0.15 $À0.24 from birth to 21 years in Dutch subjects and Tanaka et al (2004) reported values of À0.09 $À0.32 from 5.5 to 17.5 years in Japan. Zong and Li (2013) reported recently that the height references of Chinese children were significantly different compared with the World Health Organization's (WHO) growth standards. However, it is unclear which body segments of height contribute more to this difference between Chinese and other populations.…”
Section: Discussionmentioning
confidence: 98%
“…Standing height and sitting height (SH) were measured to the nearest 0.1 cm in standing position for children over 3 years old by using standardized techniques and equipment. The details of measurement of length and height had been reported previously (Zong & Li, 2013). Briefly, crownrump length was measured by an observer standing to the right of the examining table who with their left hand lifted the legs and with their right hand pushed the footboard to the sacrum, prior to recording the measured value.…”
Section: Measurementsmentioning
confidence: 99%
“…Recent tractography studies have shown significant sex‐specific differences in white matter microstructure (Hsu et al., 2008; Kanaan et al., 2012). Future studies, aimed at establishing a normal reference standard, should consider such gender differences, as is common practice in pediatric growth curves (Barbier et al., 2013; Zong & Li, 2013). Fourth, this study's laterality analysis does not include information concerning each patient's left and right handedness which is impossible to establish for the youngest subjects.…”
Section: Discussionmentioning
confidence: 99%